Monitoring MMP-2 and MMP-7 levels in traumatic wounds of the ocular adnexa (Ukrainian Journal of Ophthalmology, 2025)
Background: Matrix metalloproteinase (MMP)-2 and MMP-9 are gelatinases involved in many physiological and pathological processes including inflammation and angiogenesis, which make up the basis for tissue remodeling and repair. Prolonged inflammation and delay in healing of traumatic wounds result in postoperative cicatricial deformities. MMP-2 and MMP-9 activity monitoring might be a biomarker for healing of traumatic ocular adnexal wounds.Purpose: The purpose of the study was to assess MMP-2 and -9 levels in tissues in traumatic ocular adnexal wounds at various times after trauma.Material and Methods: We examined 60 patients presenting with traumatic ocular adnexal wounds one hour to three months after trauma. Tissue biopsy was obtained during surgical debridement of wounds and frozen. The main study group included samples of traumatized ocular adnexal tissue, and the control group, samples of healthy ocular adnexal tissue obtained during blepharoplasty. The levels of MMP-2 and MMP-9 were assessed by enzyme-linked immunoassay (ELISA). The absorbance of each well was read at a wavelength of 450 nm with a Multiskan FC plate reader, and the mean absorbance was calculated for each reference standard and sample. Samples of patients presenting with traumatic ocular adnexal wounds one hour to three months after trauma were compared with controls with regard to optical density.Results: MMP-2 and MMP-9 levels were higher in biopsy samples from traumatic wounds than in control samples. ELISA analysis found that the peak MMP-2 expression was observed at day 3 after trauma, and was 85% above the level in control samples. From day 7 to day 15, this early peak fell to a level close to (15% higher than) that of day 1. From day 15 to day 21, there was a 35 percent increase in MMP-2 expression. MMP-9 expression levels were significantly higher than MMP-2 expression levels. The peak MMP-9 expression was observed at day 4 after trauma, and was 155% above the level in control samples. From day 4 to day 7, MMP-9 expression decreased to a level 85% above the level in control samples. Thereafter, MMP-9 expression increased again to a level 100% above the level in control samples from day 8 to day 15, and gradually decreased from day 15 to day 21.Conclusion: Our study of MMP-2 and -9 levels in tissues in traumatic ocular adnexal wounds at various times after trauma demonstrated that the peak MMP-2 expression was observed at day 3, and the peak MMP-9 expression, at day 4 after trauma. The levels of both enzymes decreased at day 7, and varied thereafter. By day 21, MMP-2 and MMP-9 levels in samples taken from the wound were as low as the levels in control samples.
Keywords: MMP-2; MMP-9; traumatic wounds; wound healing; ocular adnexa; ELISA